Estudo de propriedades estruturais, ópticas e químicas de nanoestruturas semicondutoras de GaAs - Ana Clara Sampaio Pimenta (2021)
Gallium arsenide is widely studied by the scientific community, its crystalline cubic phase presents characteristics which are well established in the literature. However, when this compound is grown in nanometric dimensions, some of its properties can be changed for instance, there can be the emergence of a new crystal structure: the wurtzite (WZ). The particularities of WZ GaAs result in different electronic and vibrational structures, culminating in unobserved optoelectronic properties in relation to ZB GaAs. In the first part of this work, we studied the chemical, electronic and optical properties of doped and polytypic GaAs nanowires (NWs), by means of Raman spectroscopy (μ-RS), microphotoluminescence (μ-PL), and magneto-PL. We observed that the NWs are sensitive to excitation pump power densities (L), showing a superficial photodegradation for L = 184 kW/cm², at room temperature, which corresponds to local heating around T = 388 ºC. We realized that at this temperature value, the NW undergoes thermal oxidation and, in contrast to what has been previously reported in the literature, this process causes an abrupt loss of arsenic and the formation of polycrystalline gallium oxide. In addition to chemical properties, we investigated the radiative recombination processes in GaAs:Mg NWs with polytypism. This kind of NW exhibits different radiative recombination mechanisms, due to the axial inhomogeneity of its heterostructure. From the μ-PL at low temperatures, we verify that the main recombination mechanisms in this sample are related to the free exciton in WZ GaAs and spatially indirect excitons. We observed that these emissions are strongly disturbed by the structural disorder in the sample and are more intense for the excitation which is perpendicularly polarized with respect to the NW axis (ˆc). Also, the preliminary study with an external magnetic field oriented perpendicularly to the ˆc crystal axis suggests that the obtained results are strongly affected by the local potential fluctuations in the NW, and can’t be satisfactorily explained using the existent model. In the second part of this thesis, we studied the light-matter interaction in a strong coupling regime. We observed that the decay of exciton-polariton generates radiation with laser radiation properties, which therefore induces nonlinear effects in the ZB GaAs single quantum well (SQW). This emission was characterized and from the measurements of polarization- and pump power-resolved PL, we assessed the second harmonic generation from GaAs SQW. Finally, we concluded that the SHG efficiency is dependent on the detuning between exciton energy and cavity mode energy, revealing a significant increase in the exciton-polariton condensation condition.